Chinese Autobiographical Writing An Anthology of Personal Accounts - Ebrey, Patricia Buckley; Yao, Ping; Zhang, Cong Ellen (University of Washington Press, 2023)
Personal accounts help us understand notions of self, interpersonal relations, and historical events. Chinese Autobiographical Writing contains full translations of works by fifty individuals that illuminate the history and conventions of writing about oneself in the Chinese tradition. From poetry, letters, and diaries to statements in legal proceedings, these engaging and readable works draw us into the past and provide vivid details of life as it was lived from the pre-imperial period to the nineteenth century. Some focus on a person's entire life, others on a specific moment. Some have an element of humor, others are entirely serious. Taken together, these selections offer an intimate view of how Chinese men and women, both famous and obscure, reflected on their experiences as well as their personal struggles and innermost thoughts.With an introduction and list of additional readings for each selection, this volume is ideal for undergraduate courses on Chinese history, literature, religion, and women and family. Read individually, each piece illuminates a person, place, and moment. Read in chronological order, they highlight cultural change over time by showing how people explored new ways to represent themselves in writing.The open access publication of this book was made possible by a grant from the James P. Geiss and Margaret Y. Hsu Foundation.